Periodisasi Sejarah Hukum Adat - Sulthan, Fariz M.; Pattipeilohy, Alex Maxer; Okviany, Hana Ratlian; Satory, Agus (Advances In Social Humanities Research, 2024)
Customary law is a form of law that still exists in the lives of traditional law communities in Indonesia. The existence of customary law as a form of law whose existence is recognized in the life and legal culture of Indonesian society is stated in the 1945 Constitution of the Republic of Indonesia. Based on the background of the problem, the problem formulation is: 1) what is the periodization of the history of customary law in Indonesia? and 2) what are the benefits of studying customary law? This research uses normative juridical research methods that are qualitative in nature. The data source used is a secondary data source, while the data collection method in researching research objects is library data obtained through library research. The results of this research provide an illustration that the periodization of customary law in Indonesia consists of the Ancient era, up to around 500, the Kingdom era (from 500 to 1600), the period of influence of Islam and other religions, the Dutch East Indies period, and the period after independence. . The benefits of studying customary law are that customary law is a form of Indonesian legal culture, the position and role of customary law in national development, and customary law as a means of social control.